Irreversible profound symptomatic bradycardia requiring pacemaker after tizanidine/loxoprofen combination therapy: a case report. Issue 6 (June 2018) - Li, Xiaolin; Jin, Yunpeng
A 37-year-old man suffered irreversible profound symptomatic bradycardia requiring a pacemaker 3 days after beginning tizanidine/loxoprofen combination therapy for neck pain. This combination therapy is prescribed frequently for joint pain; however, combining loxoprofen with tizanidine could increase the risk of symptomatic bradycardia that is both permanent and severe. Similar cases have not been reported. This case suggests that tizanidine should be used cautiously when combined with loxoprofen, and drug interaction screening should be performed.